Methods and Techniques of Term Formation: A Descriptive and Analytical Study - Abu-Ras, Mohammed; Al-Sabri, Abdulrahman Al-Sabri ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2017)
The text highlights the importance of scientific terminology as keys to understanding sciences and reality, emphasizing the need for Arabic to embrace modern terms driven by global intellectual and technological advancement. It argues that Arabic, through its internal mechanisms like coinage, derivation, synonymy, and polysemy, can efficiently generate new terms. The author urges overcoming the inferiority complex some Arabic speakers hold towards their language, citing its historical success in absorbing both Eastern and Western knowledge during the era of Al-Ma'mun. The study concludes that term development follows established linguistic principles, word multiplicity fosters language growth, and precise term definition enhances clarity and communication.